Genetic Variants Associated with Gefitinib Adverse Events in Non-Small Cell Lung Cancer: A Systematic Review Integrated with Protein-Protein Interaction Network and Structural Modelling - Rangga Pradipa, Agya Marsaa; Al Ayyubi, Muhammad Shalahudin; Romadhona, Sabila; Sarkowi, Widya Khairunnisa; Nugraha, Widya Eka (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Lung cancer remains the leading cause of cancer-related death worldwide, with non–small cell lung cancer (NSCLC) accounting for approximately 85% of cases. Gefitinib is a tyrosine kinase inhibitor frequently used in NSCLC with favorable outcome. However, many patients develop severe adverse effects which might be influenced by genetic variability. Therefore, we aim to systematically review the gene variants and its association with gefitinib-related adverse effects in NSCLC patients, as well as investigate the biological process involved. Methods: A systematic search was conducted according to PRISMA guidelines across PubMed, Scopus, and Cochrane. Studies investigating the association between genetic variations with gefitinib-related adverse effects in NSCLC were included. Risk of bias was assessed using the Cochrane RoB-E. Extracted data encompassed study and patient characteristics, adverse effects, and gene variations. Significant genes identified from included studies were analyzed through PPI network analysis, and the hub proteins found were visualized through Chimera. Results: Sixteen studies involving 1,176 patients were included, with Japanese populations being the most studied. Gene variants of CYP2D6, CYP3A4, ABCB1, ABCG2, EGFR, FOXO3, IKBKB, and AKT1 were found to be associated with adverse effects such as hepatotoxicity, skin rash, and diarrhea among NSCLC patients. Metabolism and inflammatory pathways might be involved in gefitinib-related adverse effects. Conclusion: Genetic variations in CYP2D6, CYP3A4, ABCB1, ABCG2, EGFR, FOXO3, IKBKB, and AKT1 may influence gefitinib-associated adverse effects, highlighting the need of pharmacogenomic testing to guide personalized treatment and improved patient safety. Keywords: Genetic Variants, Gefitinib, Non-Small Cell Lung Cancer, Adverse Effects, Protein-protein interaction